Pendekatan Design Thinking sebagai Kerangka Desain Ulang Tampilan Laman Situs E-Commerce PT Sinar Batam Indo Perkasa - Apriyanto; Widiantoro, Suryo (Fakultas Komputer - Universitas Universal, 2024)
Designing ecommerce website is an important process of creating user interfaces and user experiences or UI/UX for an online platform that facilitates the buying and selling of products or services on the Internet. Many companies have their own e-commerce website to support their business operational. PT Sinar Batam Indo Perkasa as a ke-player in manufacture industry is facing problems with its e-commerce website in term of visual design that need to be improved to attract more costomers. In this paper we discuss how design thinking creative and user-centered approach could be implemented to redesign the visual attract of company’s e-commerce website as an innovative solution. With the utilization of Figma as a web-based graphic design tool, each phase of design thinking approach (empathize, define, ideate, prototype, and test) will be described thoroughly to produce the final result, which is an intuitive and functional design of company’s e-commerce website.